Comprovação experimental da extensão de sistemas de comunicação via rede elétrica através da tecnologia PON - Oliveira, Gianni Lima dos Santos (2023)
Through controlled experiments, the study seeks to validate the effectiveness and feasibility of applying PON (Passive Optical Network) technology to expand communication systems using existing electrical infrastructure. Implementing the combination of PON and BPL (Broadband over Power Lines) technologies for Smart Grid applications represents a significant advance in the field of smart energy networks. This combination offers an effective and viable solution for improving communication and control within power grids. PON, a passive optical network, provides high data transmission rates and reliability, enabling efficient communication between devices on a large scale. BPL, on the other hand, uses the existing electrical infrastructure to transmit broadband data, eliminating the installation of additional cables. By combining these technologies, energy networks become smarter and more responsive. PON-BPL enables high-speed data transmission over power lines, facilitating real-time monitoring, meter data collection and remote device control. In addition, this integration reduces implementation costs by using existing electrical infrastructure, eliminating the need to invest in new communications infrastructure. The network of experiments in this work was developed at the Center for Research, Innovation and Development (CPID) under a real scenario and based conceptually on smart grids. Using a three-phase low-voltage network, the consumption control information measured at the power distribution boards was collected and displayed on a dashboard installed and configured on a computer that manages the network. Downstream and upstream speeds in the order of 2 Mbit/s were obtained on the PLC physical layer and the Ethernet interface on a 137-meter-long multi-path section with 3 repeaters carrying data from the sensor installed in the electrical distribution boards in real time to the database installed in the network manager. The integration of PON-BPL technologies offers a viable and efficient technical solution for transforming traditional electricity networks into Smart Grids, improving operational performance, system reliability, enabling the implementation of triple play services, energy management services, among others.